(untitled) (KULT_online, 2018)
The volume Library Life: Werkstätten kulturwissenschaftlichen Forschens provides an insight into the practices of these places and the production of cultural knowledge. The interdisciplinary and collaborative study from eight authors is the product of work by Research Area 8 (Cultures of Knowledge, Research, and Education) at the GCSC. The authors visited scholars from the humanities and cultural studies with a broad questionnaire plumbing their individual, material, practical, medial, social, institutional, economic, political, and ideational backgrounds at their personal workspaces. The results of this survey are presented in single, issue-specific chapters. This publication delivers an important contribution to the as yet scantily researched strategies and practices in the field of cultural studies.